Three-dimensional hierarchical CuO gas sensor modified by Au nanoparticles. (February 2019) - Lei, Qi; Li, Hairong; Zhang, Huan; Wang, Jianan; Fan, Wenhao; Cai, Lina
Abstract: The three-dimensional hierarchical CuO and Au nanoparticles were synthesized by the hydrothermal method, respectively. The hierarchical CuO and the Au nanoparticles samples were characterized by X-ray diffraction and scanning electronic microscope, respectively. The as-synthesized CuO was assembled regularly from the nanosheets with thickness of 100 nm. The size of Au nanoparticles ranged from 50 to 200 nm. The hierarchical CuO gas sensors modified by different concentration of gold were fabricated. All the Au-loaded CuO gas sensors enhanced the response to ethanol and xylene while reducing the response to methanol, acetone, and formaldehyde. The results indicate that the Au nanoparticles prepared with PVP as surfactant can improve the selectivity of CuO gas sensors to ethanol gas for other common organic volatile gases. The improvement of gas sensing is mainly attributed to the different catalytic efficiency of the Au nanoparticles for different reactions. Meanwhile, the related mechanisms are discussed.